(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Bharati Mukherjee is a built up diasporic writer who has set herself among the standard American writers. She is a writer of Indian starting point who presents Indians as heroes in her fiction. Her novels for the most part describe about Indian migrants who battle to settle in an outsider nation generally America. A large portion of her novels and even short stories are composed in the American setting. Mukherjee’s recent novel, Miss New India is a special case from every last bit of her novels as it is composed in Indian foundation.